The Role of Sex Hormones and Race Disparities in Meningioma Incidence: A Comprehensive Review - Bharathiraja, Anjana (Journal of Biology and Life Science, 2024)
Meningiomas, a slow-growing tumor originating from the meninges, affect a considerable proportion of individuals worldwide and account for approximately one-third of all brain tumors. But limited research has been conducted on meningiomas, particularly regarding the role of sex hormones and race disparities in tumor incidence and prognosis. The current review summarizes the significance of sex hormones, age, and race in meningioma development and therapy. Women have a higher risk of developing meningiomas when compared to men suggesting the potential benefit of personalized treatment approaches based on sex hormone levels. Additionally, there are age-related disparities in meningioma risk, older persons have a higher risk of tumor development. Black Americans also have a higher incidence in meningiomas when compared to Americans of other races; contrary to the lower incidence rates observed in other African populations possibly due to differences in environmental and socio-economic factors. Further research is required to better understand the complex interplay between sex hormones, age, race, environmental and social factors in meningioma development. Collaborative research is crucial to address the current knowledge gaps in meningioma management and develop personalized strategies to manage this prevalent brain tumor.